Mutant Feline Sarcoma Proviruses Containing the Viral Oncogene (v-fes) and Either Feline or Murine Control Elements - Even, Jos (1983)
The sequences required for transformation by the Gardner-Arnstein (GA) strain of feline sarcoma virus (GA-FeSV) were defined by site-directed, in vitro mutagenesis of molecularly cloned proviral DNA. Portions of the Ga-FeSV provirus, subcloned in the plasmid pBR322, were mutagenized by deletion or frameshift at XhoI restriction sites flanking the nucleotide sequences presumed to encode the GA-FeSV transforming polyprotein (P108(gag-fes)). The biological activity of subgenomic and reconstructed full-genome-length molecules was assayed by transfection and focus induction in NIH 3T3 cells. Both mutant and wild-type molecules containing the intact P108(gag-fes) coding region induced foci of transformed cells at efficiencies between 10(4) and 10(5) focus-forming units per pmol of DNA; a deletion mutant lacking 3′-terminal v-fes sequences was completely nontransforming in parallel assays. Representative subcloned foci of transformed NIH 3T3 cells synthesized P108(gag-fes) with associated in vitro protein kinase activity. Focus-forming viruses could be rescued from transformed subclones induced by full-length proviral DNA, but not from cells transformed by subgenomic DNA lacking a 3′ long terminal repeat (LTR). It was concluded that: (i) nucleotide sequences encoding P108(gag-fes) and its associated kinase activity are responsible for transformation, (ii) the GA-FeSV 3′ env and LTR sequences are not required for focus induction, and (iii) the 3′ LTR is necessary for rescue of infectious FeSV RNA. A chimeric DNA containing the 5′ LTR and P108(gag-fes) coding region of GA-FeSV joined to the 3′ LTR of Moloney murine sarcoma virus was both transforming and rescuable at high efficiency. Restriction analysis showed that passaged stocks of rescued transforming virus contained Moloney murine sarcoma virus U3 sequences at both proviral DNA termini, consistent with generally accepted models for LTR formation during reverse transcription. Wild-type GA-FeSV and the chimeric virus (here designated as GAHT), each rescued from NIH 3T3 cells with the same amphotropic murine leukemia virus, yielded approximately equal numbers of foci when titrated on CCL 64 mink cells. By contrast, on mouse NIH 3T3 cells, the focus-forming titer of GAHT was 1 to 2 log higher than that of FeSV. The foci induced on NIH 3T3 cells by GAHT appeared earlier and were reproducibly larger than those induced by GA-FeSV. Differences in transforming activity on NIH 3T3 cells were also found using colony formation in agar, showing that the more rapid appearance and larger size of foci formed in liquid media were not due to virus spread. These data suggest that transcriptional control signals within the viral LTR regulate the levels of the transforming gene product in a species-specific manner.